Productivity Change and Dynamic Comparative Advantage - Nishimizu, Mieko; Page, John M. (The Review of Economics and Statistics, 1986)
This paper proposes a simple decomposition of the widely used DRC measure of international competitiveness into three distinct elements: (1) changes in international prices, (2) changes in production techniques and (3) total factor productivity change. The decomposition provides a clear analytical link between two largely separate methodologies for assessing economic performance, cost-benefit indicators based on the world price rule and total factor productivity analysis. The methodology is applied to evaluate changes in measured comparative advantage of industries in Thailand for the period 1963-76. The results broadly indicate that changes in price competitiveness and in total factor productivity are the major sources of changes in DRC ratios for Thai industries.